Photocatalytic improvement mechanism of SnO2/Sn-doped g-C3N4 Z-type heterojunctions for visible-irradiation-based destruction of organic pollutants: Experimental and RSM approaches - Yossor R. Abdulmajeed; Saad H. Ammar; Zaid H. Jabbar; Hind J. Hadi; Mohammed D. Salman; Alaa Jasim Awadh (Case Studies in Chemical and Environmental Engineering)
This work investigated the possibility of applying SnO2/Sn-doped g-C3N4 hybrid as an efficient photocatalyst for visible light-based degradation of ibuprofen (IBP). Response surface methodology (RSM) has been adopted to optimize the IBP photodegradation. The conditions were initially fixed at photocatalyst dose = 0.2 g/L, Solution pH = 7, and IBP concentration = 10 mg/L in order to assess the SnO2/Sn-doped g-C3N4 activity, which exhibited 91 % IBP destruction after 90 min. Then, the process variables (IBP concentration, pH, and photocatalyst dose) were adjusted based on the Box-Behnken Design (BBD). The experimental IBP photodegradation was exceedingly correlated with that value predicted by the obtained quadratic model (R2 = 0.993, F-value = 79.19, and P-value <0.0001). The IBP photodegradation tests exhibited that the SnO2/Sn-doped g-C3N4 dose of 0.6 g/L, solution pH of 11, and IBP concentration of 10 mg/L were the optimal values. The photocatalyst dose was specified as the major factor in the process. The boosted photoactivity was due to the created Z-type heterojunction among SnO2 and Sn-doped g-C3N4, which provides an excellent separation of photogenerated charge-carriers. Accordingly, we explored the reaction mechanism in light of trapping studies. Besides, the stability of SnO2/Sn-doped g-C3N4 hybrid photocatalyst was tested.